Product Quality Risk Analysis in the Production Process of Swa Brand Bottled Drinking Water at PT Swabina Gatra - Galuh Rossa Puspita; Gatot Kustyadji (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
Product quality is a crucial factor in the bottled drinking water industry because it is directly related to consumer health and trust. Uncontrolled production processes have the potential to create various risks that can reduce the quality of the final product. This study aims to analyze product quality risks in the production process of Swa brand bottled drinking water (AMDK) at PT Swabina Gatra. The study used a qualitative approach with a case study type, which allows researchers to understand the real conditions in the field in depth. Data collection techniques were carried out through direct observation of the production process, in-depth interviews with management and production operators, and documentation studies related to standard operating procedures and quality control. The results of the study indicate that product quality risks arise at several production stages, such as raw water treatment, filtration processes, equipment sanitation, packaging, and storage of finished products. Factors causing these risks include limited supervision, compliance with operational procedures, equipment conditions, and human resource factors. This study emphasizes the importance of implementing quality risk management systematically and continuously to minimize the potential for product defects and maintain consistent bottled drinking water quality. The research findings are expected to provide evaluation material and recommendations for companies in improving quality control systems and ensuring product safety for consumers.